1969
DOI: 10.1002/1097-0142(196908)24:2<223::aid-cncr2820240203>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Use of 5-fluorodeoxyuridine (FUDR) as an adjuvant to the surgical management of carcinoma of the stomach

Abstract: 5‐Fluorodeoxyuridine was administered to 185 patients randomized to the treated group following gastric resection for carcinoma of the stomach. Two hundred twelve patients were randomized to control groups. There are no significant differences in operative mortality, complications, or 3‐year survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…In many cancers, tumor cell proliferation is an important prognostic factor and is a key factor to monitoring efficacy of anticancer therapy. Therefore, radiopharmaceuticals directly related to cell proliferation, such as 3′-deoxy-3′-[ 18 [2]. Prior studies have established that [ 18 F]FLT uptake correlates with Ki-67 immunostaining proliferation assay, in breast cancer [3], lung cancer [4], and leukemia [5], and with S phase fraction in lung tumors as measured by flow cytometry [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cancers, tumor cell proliferation is an important prognostic factor and is a key factor to monitoring efficacy of anticancer therapy. Therefore, radiopharmaceuticals directly related to cell proliferation, such as 3′-deoxy-3′-[ 18 [2]. Prior studies have established that [ 18 F]FLT uptake correlates with Ki-67 immunostaining proliferation assay, in breast cancer [3], lung cancer [4], and leukemia [5], and with S phase fraction in lung tumors as measured by flow cytometry [6].…”
Section: Introductionmentioning
confidence: 99%
“…Here, FdUrd was used in mice at a nontoxic bolus injection of 2.5 mg/kg, while intravenous (i.v.) bolus treatment in humans is performed with 30 mg/kg [18]. We studied the effect of FdUrd in mice bearing different human tumor xenografts by biodistribution studies and animal PET.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several trials of adjuvant chemotherapy in gastric cancer (Longmire et al, 1968;Dixon et al, 1971;Serlin et al, 1969;Douglas & Stanlein, 1982;Engestrom et al, 1985;Higgins et al, 1983;Boice et al, 1983;Fielding et al, 1983) and all of these, apart from one (Douglas & Stanlein, 1982), have failed to show any benefit on survival. Indeed, two further randomised trials presented at this year's ASCO, one comparing the combination of doxorubicin and 5-fluorouracil with no treatment (Krook et al, 1988), and one comparing FAM with no treatment (Wils et al, 1988), showed no benefit from adjuvant chemotherapy.…”
mentioning
confidence: 99%
“…The majority of them gives no details on the procedure (Harrisson et al, 1989;Tonnesen et al, 1988;Moertel et al, 1984;Engstrom et al, 1985;Hugier et al, 1980;Nakajima et al, 1978;Nakajima et al, 1980;Maehara et al, 1990;Schlag, 1987;Lise et al, 1989;Allum et al, 1989c;Koyama et al, 1986;Higgins et al, 1983;Popiela et al, 1988;GITSG, 1982;Blake et al, 1981;Alcobendas et al, 1983) some lay down guidelines for surgical procedure (Coombes et al, 1990;Ochiai et al, 1983;Serlin et al, 1969;GITSG, 1982;IGTSG, 1988) or recommend a specific type of resection (Allum et al, 1989b). None had organised a pathological review of all operative specimens (Coombes et al, 1990).…”
mentioning
confidence: 99%
“…The confusion regarding interpretation of the data may even be greater when patients are not stratified according to whether they had curative surgery or not (Allum et al, 1989b;Blake et al, 1981;Ochiai et al, 1983;Serlin et al, 1969).…”
mentioning
confidence: 99%